2022
DOI: 10.6004/jnccn.2022.7055
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Access Dimensions and Guideline-Concordant Ovarian Cancer Treatment: SEER-Medicare Analysis of the ORCHiD Study

Abstract: Background: Racial disparities exist in receipt of guideline-concordant treatment of ovarian cancer (OC). However, few studies have evaluated how various dimensions of healthcare access (HCA) contribute to these disparities. Methods: We analyzed data from non-Hispanic (NH)–Black, Hispanic, and NH-White patients with OC diagnosed in 2008 to 2015 from the SEER-Medicare database and defined HCA dimensions as affordability, availability, and accessibility, measured as aggregate scores created with factor analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…66,67 Black ovarian cancer patients are less likely to receive full NCCN guideline-recommended care than NHW patients. 67 Several single-institution retrospective studies at academic centers have not shown differences in treatment or survival by race or ethnicity as seen in larger data sets, suggesting that equity can be achieved in controlled settings but may be limited by bias of who can get care at these specialized centers. 68,69 Increased geographic distance from a high-volume hospital was also associated with less concordant care.…”
Section: Differences In Receipt Of Guideline-concordant Carementioning
confidence: 99%
See 3 more Smart Citations
“…66,67 Black ovarian cancer patients are less likely to receive full NCCN guideline-recommended care than NHW patients. 67 Several single-institution retrospective studies at academic centers have not shown differences in treatment or survival by race or ethnicity as seen in larger data sets, suggesting that equity can be achieved in controlled settings but may be limited by bias of who can get care at these specialized centers. 68,69 Increased geographic distance from a high-volume hospital was also associated with less concordant care.…”
Section: Differences In Receipt Of Guideline-concordant Carementioning
confidence: 99%
“…High-quality cancer care in ovarian cancer includes adequate cytoreductive and staging surgery, receipt of timely appropriate chemotherapy, and genetic germline and tumor testing. In a large National Cancer Database study, National Comprehensive Cancer Network (NCCN) guideline nonadherence was found to be the single highest contributor to the disparity noted, explaining 36.4% of the 5-year overall survival disparity experienced by Black pateints 66,67 . Black ovarian cancer patients are less likely to receive full NCCN guideline–recommended care than NHW patients 67 .…”
Section: Ovarian Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In their SEER-based study of Americans aged < 65, Mobley and Kuo found that Black and other non-White races and those of Hispanic ethnicities have significantly higher odds of late-stage diagnosis for breast cancer compared with their White counterparts, but only Black patients have high odds of late-stage colorectal cancer diagnosis compared to White patients [ 18 ]. A national study based on SEER-Medicare database ( n = 5632) showed that 29.1% of White, 32.4% of Black, and 33% of Hispanic patients had stage 4 ovarian cancer at diagnosis, with NH-Black patients being less likely than White (hazard ratio, 0.86; 95% CI 0.75–0.99) to receive guideline-concordant systemic therapy for ovarian cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%